2012
DOI: 10.7314/apjcp.2012.13.8.3757
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin Induces Cytotoxicity in Colon Cancer Cells Via p53-independent Mechanisms

Abstract: Objective: Crocin has been proposed as a promising candidate for cancer chemoprevention. The purpose of this investigation was to investigate the chemopreventive action and the possible mechanisms of crocin against human colon cancer cells in vitro. Methods: Cell proliferation was examined using MTT assay and the cell cycle distribution fractions were analyzed using fow cytometric analysis after propidium iodide staining. Apoptosis was detected using theTUNEL Apoptosis Detection Kit with laser scanning confoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…In addition,the mice lacking the cry 1 and 2 genes lose periodicity in wheel-running behavior (Vander et al, 1999) as well as electrophysiological activity in the SCN cells under constant darkness (DD) (Bonnefont et al, 2003). In another sepatrae study, CRY1 has been previously shown to undergo aberrant DNA methylation events in Human Chronic Myeloid Leukemia (Huttmann et al, 2012;Li et al, 2012). Based on these results, we propose that inactivation of the cry1 and cry2 in glioma cells may result in deregulation of the cell cycles thus favoring the proliferation of glioma cells, as deregulated expression of the cry1 genes is common in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition,the mice lacking the cry 1 and 2 genes lose periodicity in wheel-running behavior (Vander et al, 1999) as well as electrophysiological activity in the SCN cells under constant darkness (DD) (Bonnefont et al, 2003). In another sepatrae study, CRY1 has been previously shown to undergo aberrant DNA methylation events in Human Chronic Myeloid Leukemia (Huttmann et al, 2012;Li et al, 2012). Based on these results, we propose that inactivation of the cry1 and cry2 in glioma cells may result in deregulation of the cell cycles thus favoring the proliferation of glioma cells, as deregulated expression of the cry1 genes is common in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PI3K amplification/mutation, AKT overexpression, loss of PTEN and P53 function, and overexpression of S6K1 have all been associated with cancer development and are linked to the mTOR signaling pathway (Li et al, 2012;Xu et al, 2014;Zhang et al, 2014;Zhao et al, 2014). Although mutations of mTOR itself have not been reported, mutations in components of mTOR-related signaling pathways have frequently been described in various human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…They have an inhibitory effect on the intracellular nucleic acid and protein synthesis in malignant cells as well as on protein kinase C (PKC) and pro-oncogene in INNIH/3T3 cells (Giaccio et al, 2004), which is most likely due to their antioxidant activity. Crocetin has no function in colony forming of tumor cells, but it could inhibit DNA, RNA and protein synthesis of human malignant tumor cells in a dose dependent manner (Ashrafi et al, 2005), which may be related to p53-dependent mechanisms (Li et al, 2012). In addition, crocetin could reduce interaction between hitone H1and DNA in vitro, interfere gene transcription (Magesh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%